2014
DOI: 10.1073/pnas.1411683111
|View full text |Cite
|
Sign up to set email alerts
|

Actin stress in cell reprogramming

Abstract: Cell mechanics plays a role in stem cell reprogramming and differentiation. To understand this process better, we created a genetically encoded optical probe, named actin-cpstFRET-actin (AcpA), to report forces in actin in living cells in real time. We showed that stemness was associated with increased force in actin. We reprogrammed HEK-293 cells into stem-like cells using no transcription factors but simply by softening the substrate. However, Madin-Darby canine kidney (MDCK) cell reprogramming required, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 42 publications
(71 reference statements)
5
103
0
Order By: Relevance
“…However, it was more recently shown that this might not be necessary insofar as cell lines growing in a matrix can result in high rates of reversion to stem-like cells and this could mean that pluripotency can be produced by modification of the ECM [151], a finding that remains to be replicated.…”
Section: In Vitro and In Vivo Evidencementioning
confidence: 99%
“…However, it was more recently shown that this might not be necessary insofar as cell lines growing in a matrix can result in high rates of reversion to stem-like cells and this could mean that pluripotency can be produced by modification of the ECM [151], a finding that remains to be replicated.…”
Section: In Vitro and In Vivo Evidencementioning
confidence: 99%
“…An angular-dependent probe termed Bcircularly permuted stretch-sensitive Förster resonance energy transfer( cpstFRET) was created by tandem linkage of circularly permutated yellow fluorescent protein (YFP)/Venus and circularly permutated cyan fluorescent protein (CFP)/Cerulean according to our previous reports [27]. The cpstFRET gene was inserted into the pEGFP-C1 vector (Clontech Laboratories, Mountain View, CA, USA) without the enhanced green fluorescent protein (EGFP) gene.…”
Section: Cdna Cloning and Plasmid Constructionmentioning
confidence: 99%
“…Genetically encoded optical-force probes have enabled measurement of intracellular tension in real time. Here, a probe named actin-cpstFRETactin (AcpA) was adopted according to our previous reports [27,30]. This probe is a dipole orientation-based FRET probe composed of a pair of CFP/YFP (cpCerulean/cpVenus), and can be inserted into microfilament skeletons naturally when microfilaments are under assembly in cells.…”
Section: Intracellular Structural Mechanics In Axon Growth Can Be Regmentioning
confidence: 99%
See 2 more Smart Citations